PROSPECT OF BIOMASS ENERGY FOR ELECTRICITY GENERATION IN INDONESIA - Sugiyono, Agus; Nurrohim, agus (Agency for the Assessment and Application of Technology)
Indonesia endowed with variety of energy resources both fossil and renewable. Renewable energy such as biomass has advantage in term of clean and environmentally sustainable. But utilization of biomass for electricity generation is still very small because of non-economic energy prices. The paper will present a brief result of EAEF study especially for the prospect of biomass energy in Indonesia. In the BAU scenario, coal is expected dominating as a source for electricity generation. The share of fossil fuels for electricity generation declines in the TECH scenario when compared to the BAU scenario. Biomass technology such as combustion and BIGCC contributes about 100 TWh in 2030.